Where There's Smoke There's Fire: Outdoor Smoking Bans and Claims to Public Space. (March 2013) - Bell, Kirsten
The Canadian city of Vancouver was very early to introduce extensive smokefree legislation. Smoking has been banned in all indoor locations for well over a decade and tobacco control advocates have also recently begun to push for the expansion of such legislation into outdoor spaces in the city. Drawing on a 6-month period of observation of smokers and "not-smokers" on their lunch breaks at office sites in downtown Vancouver, I examine the ways that smokers engage with outdoor public space. I show that while smokers continue to make material claims to such space, these claims have become increasingly tenuous. I argue that tobacco "denormalization" strategies provide essential context for understanding outdoor smoking bans and raise ethical questions about the form of de-facto prohibition they appear to encourage.